Successive statistical approaches for optimization of antibiotic production by nocardiopsis prasina act24 - M. KALPANA DEVI,; R.USHA, (International Journal of Pharma and Bio Sciences, 2017)
Production of secondary metabolites by microorganisms differs qualitatively and quantitatively depending on the strains and species of microorganisms used as well as on their nutritional and cultural conditions. The application of a statistical experimental design approach for the optimization of nutritional factors is one of the recent techniques that have been successfully applied to the production of various bio products. In this study we attempted to select prominent nutrient for antibiotic production by using Plackett–Burman design then further optimized the concentration based on central composite design to improve the active ingredient. In order to improve the yield of antibiotic by the new strain, Nocardiopsis prasina ACT 24 response surface methodology was employed to optimize the composition of fermentation medium. The Plackett-Burman design indicated that pH, agitation, incubation time and starch had significant effects on antibiotic production. The concentrations of these five components were investigated using Box-Behnken design and a polynomial model related to medium components concentration effect on antibiotic yield had been established. The factors optimized in the present study were useful for the increased production of antibacterial metabolite from Nocardiopsis prasina ACT24. The zone of inhibition was improved from 27mm to 30mm. The present investigation will be useful for large scale fermentation in a fermenter for the efficient production of antibiotic.